Prediction of immunodeficiency in newborn calves - Melnychuck, D. O.; Grуshchenko V. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
It is found that the most intense formation of colostral immunity in newborn calves (due colostrum immunoglobulins) occurs during the first 36 hours of life. Changes in the concentrations of immunoglobulins in the blood of infants against the backgroud of the total protein content correspond to the values of the coefficient of intensity of changes in blood immunoglobulin (CICBI). Based on the results of studies, the use of CICBI as a indicator of colostral immunity in newborn calves (CICBI norm rate is 0.14–0.16 at the 36th hour of life) is recommended.